Prevalence and associated factors of internet addiction among young adults in Bangladesh - Tubayesha Hassan; Mohammad Morshad Alam; Abrar Wahab; Mohammad Delwer Hawlader (SpringerOpen, 2020)
Abstract Background In the last decades, the use of internet has increased many folds, and internet addiction has become a severe public health issue around the world. This study aimed to determine the prevalence of internet addiction among young adults (19-35 years) in Bangladesh and to identify factors associated with it. Methods A total of 454 participants were selected from three administrative divisions of Bangladesh using multistage cluster sampling for this cross-sectional study. A self-reported questionnaire was used to collect data which included Young's 20 items internet addiction test to assess internet addiction. Results The overall prevalence of internet addiction was 27.1%. Addiction rate was 28.6% in the subgroup 19-24 years and 23.5% among 25-35 years old. In both chi-square and logistic regression analyses, internet addiction was significantly associated with living setup, time spent daily on the internet, a detached family relationship, physical activity, and smoking habit (p < 0.05). Spending time on social media websites was the most common online activity among the participants. Conclusion Our study revealed a relatively high prevalence of internet addiction among younger participants. A detached family relationship and living away from the family were significant determinants along other factors. Therefore, it is important to raise awareness among young generation and their parents towards predictors of internet addiction.